Measurement of inclusive two-particle angular correlations in pp collisions with the ATLAS detector at the LHC - Aad, G; Abbott, B; Abdallah, J; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; Abreu, H; Acerbi, E; et al. (Springer Verlag, 2012)
We present a measurement of two-particle angular correlations in protonproton collisions at √a = 900 GeV and 7TeV. The collision events were collected during 2009 and 2010 with the ATLAS detector at the Large Hadron Collider using a single-arm minimum bias trigger. Correlations are measured for charged particles produced in the kinematic range of transverse momentum pT > 100MeV and pseudorapidity |n| < 2.5. A complex structure in pseudorapidity and azimuth is observed at both collision energies. Results are compared to pythia 8 and herwig++ as well as to the AMBT2B, DW and Perugia 2011 tunes of pythia 6. The data are not satisfactorily described by any of these models.